Weight gain in mid-childhood and its relationship with the fast food environment. (10th September 2017) - Pearce, Matthew; Bray, Isabelle; Horswell, Michael
Abstract: Background: Childhood obesity is a serious public health issue. Understanding environmental factors and their contribution to weight gain is important if interventions are to be effective. Aims: The purpose of this research was to assess the relationship between weight gain in children and accessibility of fast-food outlets. Methods: A longitudinal sample of 1577 children was created using two time points from the National Child Measurement Programme in South Gloucestershire (2006/7 and 2012/13). A spatial analysis was conducted using a weighted accessibility score on the number of fast-food outlets within a 1-km network radius of each child's residence to quantify access to fast food. Results: The mean accessibility score for all children was 0.73 (standard deviation: 1.14). Fast-food outlets were more prevalent in areas of deprivation. A moderate association was found between deprivation score and accessibilty score ( r = 0.4, P < 0.01). Children who had greater access to fast-food outlets were more likely (odds ratio = 1.89, P = 0.04) to gain significant weight (>50 percentile points) compared to children who had no access to fast-food outlets. Conclusions: This paper supports previous research that fast-food outlets are more prevalent in areas of deprivation and presents new evidence on fast-food outlets as a potential contributor towards weight gain in mid-childhood.